SPE Annual Technical Conference and Exhibition 2017
DOI: 10.2118/187424-ms
|View full text |Cite
|
Sign up to set email alerts
|

Novel Application of Elemental Aluminum and Zinc to Generate aSelf-Compressing Silicate System for Use in Lost Circulation and Conformance

Abstract: Effective zonal isolation is critical in lost circulation, cement repair and conformance applications. To be successful it is often necessary to not only block pathways but also ensure a tight seal. Gaps or weak points between the blocking material and boundary layers can result in poor zonal isolation leading to gas migration, gas entrapment, and/or excessive water production among other issues. The mechanisms vary but cement, polymers, and sodium silicate can all lose volume upon setting and aging. The degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The chemistry of this product is unique and has been detailed by Millar et al, where it was investigated as a lost circulation material in drilling muds. Aqueous alkali alumino silicate provides the same benefits as sodium silicate along with some additional benefits. In the application of AAAS in the freshwater zone, a freshwater zone is not needed to be treated with a dissolved metal multivalent cation to initiate a precipitation reaction. The AAAS crystallization reaction is not affected by the presence of NaCl due to its tolerance toward salts.…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of this product is unique and has been detailed by Millar et al, where it was investigated as a lost circulation material in drilling muds. Aqueous alkali alumino silicate provides the same benefits as sodium silicate along with some additional benefits. In the application of AAAS in the freshwater zone, a freshwater zone is not needed to be treated with a dissolved metal multivalent cation to initiate a precipitation reaction. The AAAS crystallization reaction is not affected by the presence of NaCl due to its tolerance toward salts.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Miller et al applied an AAAS-based system as a lost circulation material in drilling fluids and concluded that the AAAS-based system had strong sealant characteristics. Further, it was reported in the literature that AAAS had a high tolerance toward contamination from oil, oil-based mud, and high salinity. , In addition, the alumina content in AAAS could be useful in preventing the shrinkage, as alumina content is useful as an expansion material in cement slurry and enhances the compressive strength …”
Section: Introductionmentioning
confidence: 99%
“…Further, it was reported in the literature that AAAS had a high tolerance toward contamination from oil, oil-based mud, and high salinity. 27,29 In addition, the alumina content in AAAS could be useful in preventing the shrinkage, as alumina content is useful as an expansion material in cement slurry and enhances the compressive strength. 30 In this study, a novel silicate system, AAAS, was introduced and tested on oil well cement slurry.…”
Section: Introductionmentioning
confidence: 99%